Responses of phosphine susceptible and resistant strains of five stored-product insect species to chlorine dioxide. (May 2017) - E, Xinyi; Subramanyam, Bhadriraju; Li, Beibei
Abstract: Adults of phosphine susceptible laboratory strains and phosphine resistant field strains of five stored-product insect species were exposed in vials with 0 or 10 g of wheat for different time periods to 0.54 g/m 3 (200 ppm) of chlorine dioxide gas. After exposure, adult mortality was determined 5 d later at 28 °C and 65% r.h. The 5-d mortality was 100% in laboratory and field strains of the red flour beetle, Tribolium castaneum (Herbst); sawtoothed grain beetle, Oryzaephilus surinamensis (L.); lesser grain borer, Rhyzopertha dominica (F.); maize weevil, Sitophilus zeamais Motschulsky; and rice weevil, Sitophilus oryzae (L.) that were exposed in vials with 10 g of wheat to chlorine dioxide for 26, 16, 24–34, 18–24, and 15–18 h, respectively. Corresponding exposure durations for these species and strains in vials without wheat were 15, 3, 18–20, 7–15, and 5–7 h, respectively. Dosages of chlorine dioxide producing 99% mortality (LD99 ) of T. castaneum, O. surinamensis, R. dominica, S. zeamais, and S. oryzae strains in vials with wheat ranged from 14.79−22.57, 8.20–8.41, 15.79–21.60, 10.66–14.53, and 7.67–12.20 g-h/m 3, respectively. In vials without wheat, corresponding LD99 values for T. castaneum, R. dominica, and S. zeamais strains were 6.51–8.66, 11.46–23.17, and 5.79–10.26 g-h/m 3, respectively. LD99 values for O . surinamensis and S . oryzae could not be computed, because of 100% mortality after a 3–5 h exposure to chlorine dioxide. No adult progeny production of T. castaneum and O. surinamensis was observed after 8 weeks in control and chlorine dioxide-exposed samples. Adult progeny production of Sitophilus spp. was found only in the control samples. The dosage for 99% adult progeny reduction relative to control for R. dominica strains ranged from 10.07 to 18.11 g-h/m 3 . Chlorine dioxide gas is effective in killing phosphine susceptible and resistant strains of five stored-product insect species and suppressing adult progeny production of three out of the five species. Highlights: Oryzaephilus surinamensis was most susceptible to chlorine dioxide. Rhyzopertha dominica was least susceptible to chlorine dioxide. Tribolium castaneum and Sitophilus spp. were moderately susceptible to chlorine dioxide. Phosphine resistant and susceptible strains of all species succumbed to chlorine dioxide. Adult progeny suppression was 100% only in chlorine dioxide exposed Sitophilus spp.